By His Excellency Matthew Griswold, Esquire, governor, captain general, and commander in chief, in and over the state of Connecticut. A proclamation : ... Thursday the second day of December next to be observed as a day of public thanksgiving ... Given under my hand at the Council chamber in New-Haven, the first day of November, annoque Domini 1784 (Printed by Meigs, Bowen and Dana, in Chapel-Street, 1784)
November 1, 1784 broadside issued by Governor Matthew Griswold of Connecticut, proclaiming December 2nd as a day of thanksgiving for God's bounties from the first settlement to the present.